ChemInform Abstract: 1‐Cyanoacetyl‐3, 5‐dimethylpyrazole — Effective Cyanoacetylating Agent and a New Building Block for the Synthesis of Heterocyclic Compounds. Issue 14 (20th March 2013) - Chigorina, E. A.; Dotsenko, V. V.
Abstract Review: 113 refs.